2015
DOI: 10.7860/jcdr/2015/14257.6434
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Transorbital Penetrating Injury by House-key (lock): A Case Report with a Small Review of Literature

Abstract: Penetrating injuries of the brain are quite uncommon, comprising approximately 0.4% of all head injuries. In our case, a four-year-old boy who fell forward on a house-key (lock) accidentally while playing with some other children sustained a left sided penetrating transorbital brain injury. After hospital admission, the patient had a Glasgow Coma Scale (GCS) score of 15/15, no visual loss but restriction of upward gaze (left eye) and profuse bleeding from the wound site. Firstly, the metallic key was removed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…This property of the orbit confers a unique vulnerability to penetrative cerebral injury when compared to other facial structures. [24][25][26][27][28][29][30][31][32][33][34][35] The case presented here challenges the implied notion that only penetrative injuries by rubber bullets can cause serious harm. Indeed, the patient from this case experienced complete shattering of the NOE complex extending up to the anterior skull base, causing a TBI and CSF leak.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This property of the orbit confers a unique vulnerability to penetrative cerebral injury when compared to other facial structures. [24][25][26][27][28][29][30][31][32][33][34][35] The case presented here challenges the implied notion that only penetrative injuries by rubber bullets can cause serious harm. Indeed, the patient from this case experienced complete shattering of the NOE complex extending up to the anterior skull base, causing a TBI and CSF leak.…”
Section: Discussionmentioning
confidence: 52%
“…For example, much of the literature regarding TBI due to a variety of causes centers on the relative thinness of the bony structures of the orbit. This property of the orbit confers a unique vulnerability to penetrative cerebral injury when compared to other facial structures 24–35 . The case presented here challenges the implied notion that only penetrative injuries by rubber bullets can cause serious harm.…”
Section: Discussionmentioning
confidence: 59%
“…We didn't give anticonvulsant therapy in this patient as a prophylactic altough risk of postoperative seizure is as high as 30–50%, of which 10% appear within first week of trauma because most common cause of seizure are compound depressed fracture and intracranial infection which not seen in this patient. Early surgical intervention might decrease the chance of formation of scar tissue and hence of an epileptic focus [ 21 ]. However a further investigation and follow-up must be taken due to some late complications can occur like traumatic aneurysm, the possibility of seizure in late onset as reported in Chunhua et al study that reported recurrent seizures after 30 years of pencil retained in temporal lobe at the setting of TOPI [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ещё реже данная патология осложняется проникновением ранящего агента в полость черепа, трансформи-руясь в краниоорбитальное повреждение (0,4 % от всех травм головы) [5,7,8,14,16,25,34,35,42]. В связи с этим анализ подобных клинических ситуаций представляет несомненный научный и практический интерес.…”
Section: Introductionunclassified